The Effect of Working Facility, Training and Educational Qualification to The Performance of Education Management Information System (EMIS) Operator for School at Kantor Kementerian Agama Kota Sungai Penuh - Yumaizar, Ferri (Archives of Business Research, 2019)
This research is aimed to describe empirically the effect of working facility, training and educational qualification to the performance of Operator on EMIS (Education Management Information System) for school at Kantor Kementerian Agama Kota Sungai Penuh. This is a corellative qualitative research or so called as associational research. The population of the research were 60 people who consist of all operator for school and headmaster at Kantor Kementerian Agama Kota Sungai Penuh. The sample of the research were 60 respondents. The variables of the research consist of independent variables such as working facility, training and educational qualification and dependent variable such as the performance of operator on EMIS (Education Mangaement Information System) for school at Kantor Kementerian Agama Kota Sungai PEnuh. Based on the data analysis, it was found that there is a correlation between working facility, training and educational qualification and the performance of operator on EMIS for schoold at Kantor Kementerian Agama Kota Sungai Penuh.